Why is retrieval expensive?: An analysis of component-processes - Vranić, Andrea (Array, 2011)
Research shows that division of attention during retrieval affects memory performance only minimally. This relative immunity of episodic retrieval is offset by a cost, as measured by the concurrent secondary task in a divided attention paradigm. This experiment was conducted with the aim of further exploring this relative immunity and the attentional costs associated with what seems to be obligatory retrieval processes. More specifically, we aimed at exploring the attentional cost associated with each of three retrieval component-processes: 1) cue-encoding, 2) cue elaboration, 3) retrieval mode (Tulving, 1983). A componential analysis, as introduced by Naveh-Benjamin et al. (2000), was employed to assess attentional demands of four different retrieval tasks: two tapping the episodic and two tapping the semantic memory system. Furthermore, within each of these „system tasks“, one task was data-driven and one was conceptually-driven, as proposed by the transfer-appropriate processing (TAP) approach. Our results show a similar pattern of attentional costs of the three retrieval component-processes, across various types of retrieval. The cue elaboration was found to be the most attention demanding of the three component-processes, and also this process was shown to demand significantly more attention in the non-TAP situation. These findings are interpreted within the TAP framework.